Embodied Responses to Questions-in-Progress: Silent Nods as Affirmative Answers. Issue 4 (21st April 2021) - De Stefani, Elwys
ABSTRACT: This study examines head nods produced as embodied and silent answers to polar questions before a transition relevance place has been reached. It discusses the notion of "response" and the ways in which the literature conceptualizes head nods. The analysis of video recordings of ordinary and institutional multiparty interactions shows that answer-nods rely on mutual gaze and that affirmative head nods may co-occur with other facial expressions (e.g., eye blinks). By replying with a silent head nod, respondents may complete an unfolding adjacency pair without claiming speakership, thereby enabling the questioner to extend their turn-in-progress. Alternatively, respondents may expand their answer-nod with talk, in which case silent nodding may contribute to organizing the smooth transition of turns-at-talk. Head nods produced while a question is unfolding are described as a microsequential phenomenon that may affect the questioner's turn-in-progress. Data are in French and Italian.